The Implementation of Higher Order Thinking Skills (HOTS) trough Lesson Study: A Case Study at Islamic School in Thailand - Masyhud Masyhud; Laela Hikmah Nurbatra; Sri Hartiningsih (University of Muhammadiyah Malang, 2021)
In this millennial era, Higher Order Thinking Skills (HOTS) is regarded as an important theme in education. The theme has emerged in all learning activities as it enables students to use critical thinking in their problem-solving. HOTS cannot be separated from Bloom’s Taxonomy. HOTS is important to be integrated with classes in diverse school settings. Therefore, the aim of this research is to draw the implementation of HOTS through Lesson Study. The research was conducted in one of the Islamic schools in south Thailand. The school is an Islamic Boarding School that integrates Islamic values in its learning and teaching process. Based on a preliminary interview with the school administrator, the students are coming from different economical backgrounds. As the consequence, they have a different level of cognitive and linguistic competence. Moreover, the present research was utilized a qualitative approach to describe the implementation of HOTS through Lesson Study. To acquire adequate data, participatory observation, Focused group discussion (FGD), and document analysis were used as the research instrument. The result shows that HOTS in this school in several activities such as game competitions, group discussion, and roleplay. It can guide students to expose their English skills